If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + 3y = 31 + -2y Solving 16 + 3y = 31 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. 16 + 3y + 2y = 31 + -2y + 2y Combine like terms: 3y + 2y = 5y 16 + 5y = 31 + -2y + 2y Combine like terms: -2y + 2y = 0 16 + 5y = 31 + 0 16 + 5y = 31 Add '-16' to each side of the equation. 16 + -16 + 5y = 31 + -16 Combine like terms: 16 + -16 = 0 0 + 5y = 31 + -16 5y = 31 + -16 Combine like terms: 31 + -16 = 15 5y = 15 Divide each side by '5'. y = 3 Simplifying y = 3
| r=6k-s | | 10b+3=20 | | 4(a-5)-3(2a+1)=8(a+2)+3 | | -31+7m=4(2m-7)+3 | | 0x+y+5=0 | | 7a-9b+26=0 | | Hpt=2pi | | 7a-9b+36=0 | | Hot=2pi | | 6(3x+4+2y)= | | f(x)=2x^2+14x+23 | | 85(6)x=1020 | | f(x)=4X+2X^2+8X^3 | | 15(2a-1)=2a | | T-5/2=0 | | 223.4*7.5= | | 1x+29=4x-13 | | 28(4-2h)=3h | | X+29=4x-13 | | 25x^2-9y^2+300x-126y=-684 | | 14x+5y-8z=0 | | 1.666667x=10 | | (X-7)^2/3=2 | | 0.2b+0.1s=C | | 17=x/4 | | 17-x/4 | | -28(2-y)=3y | | 5x-2(x-5)=-2+5x+8 | | 4x-9=(5x-3)/3 | | 18=2/5m | | 8u/11=-3 | | 2cos(2x)+sinx=0 |